University Choice: Implications for Marketing and Positioning - Sia, Joseph (Scientific and Academic Publishing, 2013)
The research upon which this paper was based was aimed at finding out the factors students consider important in their college choice decision and to provide marketing implications for educational administrators. Sijil Tinggi Persekolahan Malaysia (STPM), General Certificate of Education Advanced Level (GCE A-Level), United Examination Certificate (UEC), diploma holder and university foundation year participated in the study. Four hundred sixty three questionnaires were used for analysis of which the survey was based on five-point Likert scale. Results suggested that prospective students consider programme, cost (financial aid), location, high school personnel, peers and friends and campus visit as important criteria in their college choice decision. The findings have implications for private higher education institutions (PHEIs) positioning in a recruitment market, and for a reconsideration of marketing and recruitment strategy at institutional levels. Future research suggested to be carried out is on other aspects that influence student college choice decision such as university ranking, academic achievement, educational consultant, and accreditation. Also, future studies can explore a mediating variable such as parents’ expectation and encouragement on college choice decision. Lastly, exploring the college choice decision research in a qualitative manner would also be a direction of future research.